Dynamic conductivity of symmetric three-barrier plane nanosystem in constant electric field - Seti, Ju.; Tkach, M.; Voitsekhivska, O. (Condensed Matter Physics, 2011)
The theory of dynamic conductivity of nanosystem is developed within the model of rectangular potentials and different effective masses of electron in open three-barrier resonance-tunnel structure in a constant homogeneous electric field. The application of this theory for the improvement of operating characteristics of quantum cascade laser active region (for the experimentally investigated In₀.₅₃Ga₀.₄₇As/In₀.₅₂ Al₀.₄₈As heterosystem) proves that for a certain geometric design of nanosystem there exists such minimal magnitude of constant electric field intensity, at which the electromagnetic field radiation power together with the density of current flowing through the separate cascade of quantum laser becomes maximal.